Language and law in professional discourse : issues and perspectives - Bhatia, V. K. (Vijay Kumar), 1942- (Cambridge Scholars Pub., 2014)
This book provides insights into the ways in which legal professionals participate in their day-to-day activities, and critically focuses on how language is used and exploited in everyday professional discourse. It is organised into two parts dealing with topic areas of legal discourse (written and spoken) relevant to professional practice and communication. The innovative research landscape offered by this book covers diverse and complex features of legal discourse construction where social ...